Associations of physical activity type, intensity, and frequency with subclinical hypothyroidism: a cross-sectional analysis of NHANES 2007–2012 - Zeyu Li; Zeyu Li; Yu Mao; Yu Mao; Xiaoyong Wen; Xiaoyong Wen; Guangji Chen; Shiwei Zhou (Frontiers in Public Health, 2025)
ObjectiveSubclinical hypothyroidism (SCH) is a prevalent endocrine disorder associated with metabolic and cardiovascular risks. While physical activity (PA) is well recognized for its benefits on metabolic and cardiovascular health, its relationship with SCH remains unclear. This study aimed to examine the associations between different types, intensities, and frequencies of PA and SCH prevalence using nationally representative data from the U. S. National Health and Nutrition Examination Survey (NHANES).MethodsData from the 2007–2012 NHANES cycles were analyzed. Weighted univariate and multivariate logistic regression models were employed to assess the associations between PA and SCH prevalence. Curve fitting and threshold effect analyses were conducted to explore potential non-linear relationships, while subgroup analyses examined effect modifications by demographic and clinical factors.ResultsAmong 6,133 participants included in the final analysis (approximately 20.15% of the total NHANES sample), the prevalence of SCH was 2.5%. Individuals without SCH exhibited significantly higher total PA duration, particularly in occupational physical activity (OPA), vigorous physical activity (VPA), moderate-to-vigorous physical activity (MVPA), MVPA intensity, and weekly frequency of vigorous occupational physical activity (VOPA). In the fully adjusted model, each 10-h/week increase in VPA and MVPA was associated with 33% (OR = 0.67, 95% CI: 0.49–0.91) and 11% (OR = 0.89, 95% CI: 0.81–0.98) lower odds of SCH, respectively. A 10% increase in MVPA intensity was linked to an 8% reduction (OR = 0.92, 95% CI: 0.87–0.97). Similar inverse associations were found for PA and OPA (PA: OR = 0.90, 95% CI: 0.82–0.98; OPA: OR = 0.90, 95% CI: 0.81–0.99). Among PA frequency measures, only VOPA frequency was significant, with each additional session per week associated with a 17% reduction in odds (OR = 0.83, 95% CI: 0.74–0.94). Curve fitting analysis revealed a non-linear relationship between MVPA intensity and SCH prevalence, with a threshold at 57.14%. Below this threshold, higher MVPA intensity was associated with lower SCH prevalence (p = 0.001), whereas above this threshold, the association became non-significant. Subgroup analyses identified a significant interaction with age, where the protective effects of PA and OPA were significant only in individuals aged <60 years.ConclusionThis study suggests that higher PA levels, particularly at greater intensities and frequencies, are associated with a lower prevalence of SCH, especially in individuals aged <60 years. These findings highlight the potential role of regular, high-intensity PA in reducing SCH risk.